2015
DOI: 10.11648/j.ejb.20150303.11
|View full text |Cite
|
Sign up to set email alerts
|

UV Absorbance of Aqueous DNA

Abstract: Abstract:The UV absorption spectra of water with different electric charge (potential) were obtained. It was shown that UV absorption spectra of water with negative electric charge (potential) have the sharp peaks with maximum in the range 190 -200 nm and UV absorption spectra of water with positive electric charge (potential) have the wide peaks with maximum in the range 200 -220 nm. It was asked to explain this absorption. It was also established that UV absorption spectra of water solutions of surface inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 8 publications
(7 reference statements)
0
12
0
Order By: Relevance
“…On the contrary, the negative electrification of water leads to the appearance of a peak with a maximum at ~ 195 nm on the same spectra. It should also be taken into account that uncharged water does not have a significant absorption of UV radiation in the range from 180 to 240 nm [12]. As a result, using this relationship, it was found that the contact of water with these feathers is always accompanied by the appearance of significant absorption at 205 -210 nm on the UV spectra of water absorption.…”
Section: The Flying Insects and Birdsmentioning
confidence: 99%
“…On the contrary, the negative electrification of water leads to the appearance of a peak with a maximum at ~ 195 nm on the same spectra. It should also be taken into account that uncharged water does not have a significant absorption of UV radiation in the range from 180 to 240 nm [12]. As a result, using this relationship, it was found that the contact of water with these feathers is always accompanied by the appearance of significant absorption at 205 -210 nm on the UV spectra of water absorption.…”
Section: The Flying Insects and Birdsmentioning
confidence: 99%
“…Feather research perspectives Based on the results obtained, to create a DNA model that better reflects the morphological features of real DNA. So, it can be waiting that thanks to the most successfully DNA models can be explained of a number of properties of real DNA, including their melting, as well as the nature of hypo-and hyperchromic effects in the UV absorption spectra of aqueous DNA solutions [4,[28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…Precipitation was carried out in open vials stored in the dark. Under such conditions, the solution acquires a negative potential, which reduces the solubility of DNA and promotes its precipitation [4][5][6].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations